Paisagens, ambiências e situações comunicativas na Praça da Savassi: fabulações e disputas na produção do espaço da cidade - Juliana Lopes Dias (2017)
This doctoral thesis proposes to analyze the how the urban space is produced and disputed by different actors, especially through communicative practices. To this end, it is intended to discuss the intentions of the physical constitution of urban spaces and how to handle the relationship between the morphology and the uses and appropriation of space by citizens. Understanding that global capital is present in a variety of ways, including through interventions in the physical space at points of high significance of the cities, we are interested in how the communicative interactions engage with the landscape and the communicative ambience and how the communication processis connected with the process of adaptation and resistance that (re)configure these spaces, specially the squares. It was chosen as the object of study the Savassi Square, in Belo Horizonte, where we seek evidence of how the communicative situations that takes place in urban space are affected by the characteristics of the contemporary landscape - being embarrassed, inhibited, limited; or contributing to (re)establish the relations of citizens with these spaces. We used the methods of documentary analysis, survey, participant observation and cartographic drift - unplanned journeys through the landscape, as proposed by the Situationist International. Among the main results, we highlight that the construction of the spaces of the city is influenced by the attempts to create and recreate the places by many actors, including: those who has the authority on the places; others that, in spite lacking that power, know how to use then in many ways; and the citizens, on their everyday lives, built on the place. The notion of communication as a attempt helps us to demonstrate how the tales, marketing strategies and interventions, among others, influence the senses that pass through the places without, however, define it.